Results following the use of a closed system (S3) for vitrification of human blastocysts - Wiemer, Klaus (2015)
This paper describes the use of a closed vitrification system that is easy to use and allows the blastocysts to be vitrified in a closed secure container. This system does not use dimethylsulphoxide (DMSO) as a cryoprotectant as well. This system is referred to as S3 vitrification. Human blastocysts were vitrified on Days 5 and 6 (Day of retrieval equals Day 0). Only high quality full blastocysts or greater in development were preserved. A total of 139 transfers have been performed with an overall survival rate of 81%. The delivery/ongoing pregnancy rates are 58% with a 48% implantation rate for all patients in all age groups. The overall outcomes achieved with this closed system are encouraging.